Crowdfunding: A New Approach to Entrepreneurship's Startup Phase - Noor, Md Asad; Hossain, Tanjela; Shirazi, Hasan (ABC Journal of Advanced Research, 2022)
Investors may support new commercial, cultural, or social enterprises in exchange for future commodities and activities. Crowdfunding is an essential part of project finance right now. Many people are intrigued about how crowdfunding works and how it may help start new businesses. Still, there is a lack of understanding and expertise on how crowdsourcing works and how it may assist these new initiatives to be successful. The most challenging task is obtaining financial support before establishing an entrepreneurial or creative venture. If the developer lacks links to venture capitalists or banks and a solid financial track record or commitment, they may have trouble getting project funding. This article explains crowdsourcing, a new kind of finance for company owners and project creators. According to this survey, the industry is not mainly established. Instead, it outlines CF's qualities and critical players. Crowdfunding enables a creative or patronage concept to be realized by collecting finances from many people online. Crowdfunding may be the answer for businesses or creatives that need resources. Research has uncovered many crowdsourcing business concepts and finance sources. We used empirical data to evaluate how it would assist capital deficit units and the strategy's merits and downsides from the founders, funders, and platform perspectives.